Current Problems With Car Tires For Fire and Rescue Equipment Operation - N.Ya.Makhkamov; Sh.B.Asamov (European Journal of Life Safety and Stability (2660-9630), 2023)
The article analyzes the operation of tires of fire and rescue vehicles, tire wear from the impact of an aggressive road surface, influx of thermal shock, road class and climatic conditions. Recommendations are given for calculating the service life of tires for fire and rescue equipments